Ultralow Dispersion Multicomponent Thin‐Film Chalcogenide Glass for Broadband Gradient‐Index Optics. Issue 39 (13th August 2018) - Kang, Myungkoo; Swisher, Andrew M.; Pogrebnyakov, Alexej V.; Liu, Liu; Kirk, Andrew; Aiken, Stephen; Sisken, Laura; Lonergan, Charmayne; Cook, Justin; Malendevych, Teodor; Kompan, Fedor; Divliansky, Ivan; et al.
Abstract: A novel photothermal process to spatially modulate the concentration of sub‐wavelength, high‐index nanocrystals in a multicomponent Ge‐As‐Pb‐Se chalcogenide glass thin film resulting in an optically functional infrared grating is demonstrated. The process results in the formation of an optical nanocomposite possessing ultralow dispersion over unprecedented bandwidth. The spatially tailored index and dispersion modification enables creation of arbitrary refractive index gradients. Sub‐bandgap laser exposure generates a Pb‐rich amorphous phase transforming on heat treatment to high‐index crystal phases. Spatially varying nanocrystal density is controlled by laser dose and is correlated to index change, yielding local index modification to ≈+0.1 in the mid‐infrared. Abstract : High‐precision achromatic gradient‐refractive‐index (GRIN) optical elements are manufactured by a cost‐effective and scalable approach. A novel photothermal process is utilized to spatially modulate the concentration of sub‐wavelength, high‐index nanocrystals within chalcogenide thin‐film glasses, composed of Ge‐As‐Pb‐Se, thereby achieving ultralow dispersion over an unprecedented bandwidth and enabling control of arbitrary index gradient for GRIN optics.